A constituição da área disciplinar de didáctica das línguas em Portugal - Alarcão, Isabel (Linguarum Arena, 2018)
The visibility gained by Language Didactics in Portugal in the past thirty years has justified its constitution as a disciplinary field institutionalised within higher education. Built on a personal and experiential view, though filtered by other perspectives and conclusions in a number of studies, this text aims at establishing the context for the emergence of the area as such, describing its development trajectory and raising some problematic issues. The relation that originally connected the area to Applied Linguistics is pointed out, as well as the gradual process that led to its autonomy and the construction of a disciplinary identity. This process is presented as one that developed as the understanding of the research object revealed the interest in creating articulations with other domains, in order to obtain answers to questions that Language Didactics identified as its own. The formative dimension of the discipline is addressed in its relation to teaching practice and teacher education; but the development of research allowed by the scientific blooming in the national context is also underlined. The impact of phenomena related to the advances of information technologies and to globalisation is recognised, namely the effects that resulted from the integration of Portugal as a member in the European Union. Other signs of transformation in the epistemological journey of the discipline are acknowledged, identifying interlinguistic, interdisciplinary and interprofessional frontiers that tend to fade and revealing Language Didactics as a field that opens to new spheres of action; still, there are warnings against uncontrolled openness that could lead to loss of identity. At the end, a conceptual framework is presented, as a summary and a possible organiser of a deeper historical and epistemological characterisation of this disciplinary field.